(untitled) (Academic Journal of Internal Affairs, 2021)
According to the Hungarian Criminal Code, there is no possibility for a court to impose a fine and expulsion against the same perpetrator at the same time simultaneously. Although both the regulation of fine and expulsion contain rules which state that the imposition of these penalties is mandatory in some special cases. In this study, after detecting the problem I present the contradictory case law and then the legislator’s attempt for a solution. Finally, for the reassuring elimination of discrepancy, I suggest my own de lege ferenda proposal. Arrived: 9 November 2020 Accepted: 24 November 2020